William W. Mansfield, A Digest of the Statutes of Arkansas: Embracing All Laws of a General and Permanent Character in Force at the Close of the Session of the General Assembly of One Thousand Eight Hundred and Eighty-three Page 490 (Vol. 1, 1884) §1909 - (:unkn) unknown (General Publisher, 1884)
Prohibited the sale, barter, exchange, disposal or furnishing, or keeps any dirk, Bowie-knife, sword or spear in a cane, brass or metal knuckles, or any kind of pistol or cartridge. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER & POSSESSION